PYRAMIDELLIDOS (MOLLUSCA, GASTROPODA) EN SEDIMENTOS HOLOCENOS DE BAHIA BLANCA, ARGENTINA (Ameghiniana, 2013)
PYRAMIDELLIDS (MOLLUSCA, GASTROPODA), IN THE HOLOCENE SEDIMENTS OF BAHIA BLANCA AREA. ARGENTINA. Several specimens of small gastropods corresponding to the Family Pyramidellidae are described and illustrated in this paper. They were obtained from Holocene sand shell ridges in the Bahía Blanca area. The Pyramidellidae comprises a taxonomically confused group. Turbonilla atypha, Turbonilla abrupta, Turbonilla inciso, Turbonilla conradi, Turbonilla haycocki, Odostomia impressa y Peristichla agria are species that have not yet been surveyed in the living fauna of the adyacent coast. Several species previously known only from recent material are mentioned for the first time as fossils: Turbonilla atypha, Turbonilla abrupta, Turbonilla elongata, Turbonilla interrupta, Turbonilla incisa, Turbonilla pyrrha, Turbonilla conradi, Turbonilla haycocki, Turbonilla sanmatiensis, Odostomia impressa, Eulimella bahiensis y Peristichia agria. This is the first mention of the genus Peristichia in Argentina.